Tinea capitis occurring in adults – a report of two cases with atypical presentation - Priyanka, Sunkavalli; Gopal, K. V. T.; Raju, P. V. Krishnam; Rani, B. Rekha (International Journal of Research in Dermatology, 2026)
Tinea capitis (TC) is a dermatophytic infection affecting the scalp hair and skin. It occurs primarily in children between 3 and 14 years of age, but it might affect any age group. Herein, we report 2 cases of adult tinea capitis who presented with atypical clinical features like pustules, crusted scaly plaques and non-scarring alopecia. Various investigations including potassium hydroxide (KOH) mount, dermoscopy, histopathological examination, hemogram, serum biochemistry and viral screening were conducted. Based on clinicopathological correlation both the cases were diagnosed as Tinea capitis. The patient received treatment with oral Griseofulvin along with topical luliconazole cream resulting in complete resolution of lesions.